Sorption of G-agent simulant vapours on human scalp hair. (1st August 2020) - Côte, Clémentine; Piram, Anne; Lacoste, Alexandre; Josse, Denis; Doumenq, Pierre
Abstract: Human scalp hair is a biological matrix that can trap chemical vapours from explosives (TNT), drugs (THC) and chemical weapons (yperite). The external contamination of human's hair following exposure to organophosphorus (OP) nerve agent was simulated by model compounds: triethyl phosphate (TEP) and diisopropyl fluorophosphate (DFP). In this work were exposed strands of hair to vapours of TEP and DFP (3 and 7 ppmv ) to model sorption kinetics. Sorption isotherms were also investigated at several contamination levels (80–3000 mg min.m −3 ). OP nerve agent simulants were extracted from hair by soaking in DCM. Raw extracts were analysed in GC-MS/MS to quantify each simulant content in hair. Results were fitted by applying isotherm or kinetic equations. The best model was found to be bimodal first-order, suggesting the co-existence of two different mechanisms of sorption. The best equation to describe OP vapours incorporation on hair was Freundlich model. Thus hair can be used as a passive sensor able to trap chemical G-agents and can also offer valuable information regarding both individual contamination and proof of exposure to chemical weapons. Highlights: Scalp hair can be used as a passive sensor able to trap organophosphorous agents. Sorption kinetics are best fitted by a bimodal first‐order model. Sorption isotherms follow Freundlich model. Qualitative and quantitative informations can be expected in the field.